Unveiling the roles of lattice strain and descriptor species on pt-like oxygen reduction activity in Pd-Bi catalysts - Sarkar, Shreya; Ramarao, S. D.; Das, Tisita; Das, Risov; Vinod, C. P.; Chakraborty, Sudip; Peter, Sebastian C. (ACS Catalysis, 2021)
A facile non-template-assisted mechanical ball milling technique was employed to generate a PdBi alloy catalyst. The induced lattice strain upon the milling time caused a shift of the d-band center, thereby enhancing the oxygen reduction reaction (ORR) catalytic activity. Additionally, the Pd-O reduction potential and adsorbed OH coverage used as descriptors stipulated the cause of the enhanced ORR activity upon the increased milling interval. Redox properties of surface Pd are directly correlated with a positive shift in the Pd-O reduction potential and OH surface coverage. Hence, by deconvoluting the lattice strain and the role of the descriptor species we achieved a catalyst system with a specific activity 5.4X higher than that of commercial Pt/C, as well as an improved durability. The experimental observation is well-corroborated by a theoretical simulation done by inducing strain to the system externally.
Keywords: charge-transfer; electrocatalysis; fuel cell; Lattice strain; oxygen reduction; Pt-like activity

Unraveling the cooperative mechanisms in ultralow copper-loaded WC@NGC for enhanced CO2 electroreduction to acetic acid - Bagchi, Debabrata; Riyaz, Mohd; Raj, Jithu; Roy, Soumyabrata; Singh, Ashutosh Kumar; Cherevotan, Arjun; Vinod, Chathakudath P.; Peter, Sebastian C. (Chemistry of Materials, 2024)
Electrochemical CO2 reduction reaction (eCO(2)RR) has been explored on tungsten carbide (WC) nanoparticles embedded on N-doped graphitic carbon (NGC), demonstrating excellent activity toward the formation of acetic acid at an extremely lower potential. The activity has been further enhanced by loading ultralow copper sites into the catalyst system, exhibiting 80.02% Faradaic efficiency (FE) toward acetic acid at an applied potential of -0.3 V (vs RHE). Potential-dependent in situ infrared (IR), X-ray photoelectron spectroscopy (XPS), Raman spectroscopy, ex situ extended X-ray absorption fine structure (EXAFS) studies, and computational analysis confirm that synergy between uniformly dispersed Cu atoms and WC lattice plays a crucial role in the formation of acetic acid with high FE at a lower potential. It has been observed that the W atom of WC strongly chemisorbs CO2 with a significant change in the C-O bond length and the O-C-O bond angle, in contrast to weaker adsorption on Cu-based catalyst surfaces. The presence of a Cu site enhances the adsorption of CO2, thereby increasing the possibility of C-C coupling kinetically. Most importantly, hydrogen evolution predominates on the catalyst's surface at higher applied potentials (-0.5 to -1.1 V vs RHE), elucidating the mechanism underlying enhanced charge transfer between copper and WC, a phenomenon ascertained through in situ IR spectroscopy and ex situ XPS analysis